Same and other : negotiating African identity in cultural product ion - Baaz, Maria Eriksson; Palmberg, Mai. (Uppsala : Nordiska Afrikains[sic]itutet, 2001)
The idea of African Otherness has occupied a central role in discour ses on cultural production in Africa, whether film, literature, music o r the arts.
Includes bibliographical references.
Keywords: Ethnicity in art. -- Africa; Arts -- Africa